Genetic Analysis of Patients Who Experienced Awareness with Recall while under General Anesthesia. (November 2019) - Sleigh, Jamie W.; Leslie, Kate; Davidson, Andrew J.; Amor, David J.; Diakumis, Peter; Lukic, Vesna; Lockhart, Paul J.; Bahlo, Melanie
Abstract : Background: Intraoperative awareness with recall while under apparently adequate general anesthesia is a rare, unexplained, and often very distressing phenomenon. It is possible that a relatively small number of genetic variants might underlie the failure of general anesthetic drugs to adequately suppress explicit memory formation and recall in the presence of apparently adequate anesthesia concentrations. Methods: The authors recruited 12 adult patients who had experienced an episode of intraoperative awareness with recall (compared with 12 controls), performed whole exome sequencing, and applied filtering to obtain a set of genetic variants that might be associated with intraoperative awareness with recall. The criteria were that the variant (1) had a minor allele frequency less than 0.1% in population databases, (2) was within exonic or splicing regions, (3) caused a nonsynonymous change, (4) was predicted to be functionally damaging, (5) was expressed in the top 50% of genes expressed in the brain, and (6) was within genes in Kyoto Encyclopedia of Genes and Genomes pathways associated with general anesthesia, drug metabolism, arousal, and memory. Results: The authors identified 29 rare genetic variants in 27 genes that were absent in controls and could plausibly be associated with this disorder. One variant in CACNA1A was identified in two patients and two different variants were identified in both CACNA1A and CACNA1S. Of interest was the relative overrepresentation of variants in genes encoding calcium channels and purinergic receptors. Conclusions: Within the constraints of the filtering process used, the authors did not find any single gene variant or gene that was strongly associated with intraoperative awareness with recall. The authors report 27 candidate genes and associated pathways identified in this pilot project as targets of interest for future larger biologic and epidemiologic studies. Abstract : A preliminary study sought to determine whether there is evidence that awareness with recall is caused by a few rare variants with high penetrance in 12 patients who had experienced awareness with recall in the presence of apparently adequate anesthesia. Whole exome sequencing was conducted and identified variants were filtered and prioritized to identify a candidate list that might be suitable for further investigation of causes of awareness with recall. No candidate gene(s) suggestive of a monogenic etiology were identified, possibly because of the application of a filtering strategy, the small sample size, or use of exome sequencing, which does not interrogate potentially important regulatory noncoding sequences.Supplemental Digital Content is available in the text.